Dukungan Minat, Fasilitas, dan Pola Asuh dalam Belajar terhadap Kemandirian serta Dampaknya pada Hasil Belajar Matematika Kelas VIII SMP Muhammadiyah 7 Surakarta - Astuti, Ayu Widi; , Prof.Dr. Sutama, M.Pd (2017)
Mathematics learning outcomes is important. Learning outcomes can be regarded as a changes in behaviour and ability that acquired through students activities after learning. But, in fact its still needed to increase because the learning outcomes has a variation. Variation in mathematics learning outcomes caused by interest in learning, learning facilitie, and pattern in parenting. Previous relevant research not yet be able to answer this problems, so its necessary to do a research. This research aims to examine (1) contribution of interest in learning, learning facilities, and parenting toward mathematics learning outcomes indirectly through self regulated in learning; (2) contribution of interest in learning, learning facilities, and parenting toward self regulated in learning; (3) contribution ofself regulated in learning toward mathematics learning outcomes. This is a quantitative research using correlational research method. Population in this research are 159 students. Sample was collected through proportional random sampling with lottery. Sample in this research are 114 students. Data for mathematics learning outcomes was collected through documentation and data for interest in learning, learning facilities, and pattern in parenting using questionnaire method. The data analysis technique using path analysis.Prerequisite test that must be done are normality test, linearity test, multikolinearity test, autocorrelation test, and heteroskedastisitas test. Data research from 7 Muhammadiyah Junior High School of Surakarta in high, medium, and low category, disposed have a mathematics learning outcomes in medium category with 68,42%. Independence learning in medium category with 64,04%. Interest in learning its also medium category with 63,16%. Learning facilities in medium category with 69,3%. Pattern parenting in medium category with 62,28%. The results showed that (1) There is a contribution interest in learning, learning facilities, and parenting that significant toward mathematics learning outcomes indirectly through self regulated in learning, the contribution is 33,8%; (2) There is a contribution interest in learning, learning facilities, and parenting that significant toward self regulatedin learning, the contribution is 47,5%; (3) there is a contribution self regulated in learning toward mathematics learning outcomes,the contribution is 21,2% but isn't significant in α=5%. Keywords: learning facilities; learning outcomes; self regulated; interest in learning; parenting